A Novel Approach for Solving Fuzzy Differential Equations Using Cubic Spline Method. (22nd May 2021) - Karpagappriya, S.; Alessa, Nazek; Jayaraman, P.; Loganathan, K.
Abstract : Ambiguity in real-world problems can be modeled into fuzzy differential equations. The main objective of this work is to introduce a new class of cubic spline function approach to solve fuzzy initial value problems efficiently. Further, the convergence of this method is shown. As it is a single-step method that converges faster, the complexity of the proposed method is too low. Finally, a numerical example is illustrated in order to validate the effectiveness and feasibility of the proposed method, and the results are compared with the exact as well as Taylor's method of order two.